2022
DOI: 10.1136/tobaccocontrol-2021-057071
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating US smokers’ willingness to pay for different cigarette packaging designs before and after real-world exposure in a randomised trial

Abstract: IntroductionRemoval of tobacco industry branding from cigarette packs may reduce their appeal. Adding graphic warning labels (GWLs) should enhance this effect. We investigate whether willingness to pay for various packaging designs changes after 3 months’ use of: (1) US branded packs without GWLs (US), (2) non-branded packs without GWLs (Blank), and (3) rotating non-branded packs with GWLs (gangrene; throat cancer; neonatal baby) covering >75% of pack (GWL).MethodsCalifornian adult daily smokers not plannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…When first exposed to the different package designs before randomization, participants demonstrated considerable aversion to the GWL packs compared with the blank and standard US packs used in the other study arms, 19 and these reactions were confirmed by an online willingness to pay study that explored purchase choices when multiple different packaging options were varied. 31 If this aversive reaction prompted smokers in the GWL pack group to hide their packs, we might expect an immediate increase in pack hiding after participants received their study packs. However, it took weeks to reach a stable level of pack hiding, which was then maintained throughout the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…When first exposed to the different package designs before randomization, participants demonstrated considerable aversion to the GWL packs compared with the blank and standard US packs used in the other study arms, 19 and these reactions were confirmed by an online willingness to pay study that explored purchase choices when multiple different packaging options were varied. 31 If this aversive reaction prompted smokers in the GWL pack group to hide their packs, we might expect an immediate increase in pack hiding after participants received their study packs. However, it took weeks to reach a stable level of pack hiding, which was then maintained throughout the intervention.…”
Section: Discussionmentioning
confidence: 99%